The impact of identity on anxiety during wiki editing in higher education. Issue 1 (2014) - ,; ,
Abstract : Purpose – Although wikis are common in higher education, little is known about the wiki user experience in these contexts and how system characteristics impact such experiences. The purpose of this paper is to explore experimentally the hypothesis that changing the anonymity of identity when editing wikis will impact significantly on user editing anxiety and that this may be dependent on the type of edit being conducted.Design/methodology/approach – This hypothesis was explored using a controlled experiment study whereby users were given excerpts to include in their own words on a wiki site used for a psychology course. Users edited the wiki anonymously, using a pseudonym relevant to the context (a matriculation number) and using a full named identity. Users were also either asked to add content to the wiki or to delete and replace content on the wiki site.Findings – The paper found that users experienced significantly less anxiety when editing anonymously compared to when editing with a pseudonym or full name and that the type of edit being conducted did not impact the anxiety felt.Originality/value – The research highlights that the effects of anonymity discussed are also in operation in a wiki context, a more fundamentally anonymous context compared to blogs, bulletin boards or general computer‐mediated communication tools. Acknowledgements : The authors would like to thank Russell Beale and Finn Donaldson for their comments on previous drafts of this manuscript. The research was funded by an EPSRC DTA studentship and EPSR PhD+ Fellowship.